Fishermen community’s surviving strategy in facing climate change challenge in Kebonagung District Pacitan Regency Indonesia - Permatasari Putri; Wibowo Agung; Suwarto; Winarno Joko; Wijianto Arip (BIO Web of Conferences)
Coastal people live dependently on nature. The change of nature condition has an impact on fishing activity. Damaged sea ecosystem affects the sea biota life and endangers fishermen’s livelihood. Uncertain income leads to the less fulfilled economic need. Considering this problems, this research aims to formulate a strategy used by fishermen to face climate change challenge. The research taken place in Kembang and Gawang Villages, Pacitan Regency used qualitative method with case study approach. Data were collected through interview, observation, and documentation. SWOT analysis was used to formulate strategy by identifying strengths, weaknesses, opportunities, and threats. The research found that fishermen’s persistence and experience with fishing should be optimized through training and facilitation strategies to face the condition of climate change. The organizing strategy through fishermen group can facilitate the activity of extension concerning technology application and improvement of social relation with other stakeholders. This study recommends the importance of cooperation between stakeholders to support the sustainability of fishermen’s fisheries businesses in facing the challenges of climate change by optimizing existing potential.